Compositional nanodomain formation in hybrid formate perovskites. Issue 81 (28th September 2017) - Donlan, Edwina A.; Boström, Hanna L. B.; Geddes, Harry S.; Reynolds, Emily M.; Goodwin, Andrew L.
Abstract : We discover compositional nanodomains in mixed-metal hybrid formate perovskites that are conceptually related to polar nanoregions in relaxor ferroelectrics. Abstract : We report the synthesis and structural characterisation of three mixed-metal formate perovskite families [C(NH2 )3 ]Cu x M1− x (HCOO)3 (M = Mn, Zn, Mg). Using a combination of infrared spectroscopy, non-negative matrix factorization, and reverse Monte Carlo refinement, we show that the Mn- and Zn-containing compounds support compositional nanodomains resembling the polar nanoregions of conventional relaxor ferroelectrics. The M = Mg family exhibits a miscibility gap that we suggest reflects the limiting behaviour of nanodomain formation.